Numerical investigation into impact of halide perovskite material on the optical performance of prism-loaded hybrid surface plasmon resonance biosensor: A strategy to increase sensitivity - Roy, Sourav; Mondol, Nibir; Kundu, Diponkar; Meem, Anisha Anjum; Islam, Md. Rasidul; Hossain, Md. Amzad; Hossain, Md. Biplob (Sensing and Bio-Sensing Research, 2024)
The technology of surface plasmon resonance (SPR) is widely recognized and valued for its ability to rapidly and sensitively investigate biomolecular interactivities in real-time. Herein, we numerically investigate the collective influence of metal/ transition metal dichalcogenide (TMDC)/halide perovskite (HP)/2D carbon (C) and phosphorus (P) allotropes on the functionality of an SPR biosensor deploying Kretschmann configuration. The incident light wavelength is held constant at 633 nm, and radiative properties of the hybrid structure are determined using the attenuated total reflection and transfer matrix techniques. Crucial performance metrics such as quality factor (QF), figure of merit (FoM), sensitivity, and detection accuracy are calculated. The comparison is conducted and evaluated against the current literature using performance outcomes in terms of several prisms such as BK7, BAK1, BAF10, SF5, SF10, SF11, 2S2G, CaF2, and CsF, several TMDCs such as WS2, MoS2, WSe2, MoSe2, and PtSe2, several HPs such as CsPbI3, KSnI3, CsSnI3, and FASnI3, and 2D C/P allotropes such as Graphene, MXene, Black phosphorene (BP), and Blue phosphorene (BlueP) in order to search optimum parameters, and then we implement the best one in each layer of this biosensor design. It is noticed that the SPR heterostructure based on BAK1 prism, plasmonic metal Ag, tungsten disulfide (WS2) TMDC, formamidinium tin iodide (FASnI3) HP and 2D BP exhibits outstanding performance with regard to sensor performance characteristics. The observed FoM and sensitivity are 48.2/RIU and 402°/RIU, respectively. The investigation of the electric field distribution within this biosensor along the normal to the interface is also conducted using the finite difference time domain (FDTD) approach to demonstrate the unique contribution of FASnI3. The findings presented in this study are anticipated to play a key role in the improvement of plasmonic resonance-based biosensing domains like DNA hybridization or formalin detection by employing halide perovskite as an additional layer in SPR biosensors.